2020
DOI: 10.3390/pharmaceutics12010043
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Nanoparticles-Loaded Chitosan/Chitooligosaccharide Microparticles and Their Antioxidant Potential: A Chemical and In Vivo Investigation

Abstract: Selenium nanoparticles (SeNPs) have attracted attention due to their favorable properties, unique bioactivities, and potential for use in nutritional supplements and nanomedicine applications. However, the application of SeNPs in the clinic has been greatly hindered by their poor stability, and their potential to protect against alcohol-induced oxidative stress has not been fully investigated. Herein, SeNPs were synthesized in the presence of chitosan (CS) or chitooligosaccharide (COS), and a mixture of SeNPs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…As presented in Figure 6, the serum and hepatic Se levels in the Se-supplementation groups were significantly higher than those of other groups (p < 0.05), indicating that CS-SeNPs might enhance the Se stock in the animals. This is in line with the reported efficient Se-retention capacity of some SeNPs stabilized by other macro-molecules [2,3,25,40] or microorganisms [17], confirming the potential of nanoparticles in Se supplementation. Se retention by extra Se supplementation needs to be discussed.…”
Section: Se Retentionsupporting
confidence: 88%
See 2 more Smart Citations
“…As presented in Figure 6, the serum and hepatic Se levels in the Se-supplementation groups were significantly higher than those of other groups (p < 0.05), indicating that CS-SeNPs might enhance the Se stock in the animals. This is in line with the reported efficient Se-retention capacity of some SeNPs stabilized by other macro-molecules [2,3,25,40] or microorganisms [17], confirming the potential of nanoparticles in Se supplementation. Se retention by extra Se supplementation needs to be discussed.…”
Section: Se Retentionsupporting
confidence: 88%
“…The DPPH radical (•DPPH) and superoxide anion radical (•O 2 − ) scavenging assays were performed as previously described [25] to measure the antioxidant abilities of the tested samples. In addition, the hydroxyl radical (•OH) scavenging activity was determined according to Peralta [26], with some modification.…”
Section: Free-radical Scavenging Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many investigations that have proven that antioxidant administration decreases augmented lipid peroxide in diabetic rats (El-Alfy et al, 2005) and hyperlipidemia and vascular damage in ApoE-knockout mice (Guo et al, 2019). Furthermore, Bai et al (2020) recently reported that SeNPs have a potent antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that LS-COS-Se showed the better biological activity. But there were no significant difference in the ADFI, ADG and F/G of chickens during the experimental period of 4 weeks in vivo.COS is a positively charged alkaline antioxidant, which scavenges free radicals and promotes metabolism by absorbing all kinds of negatively charged toxic substances[21,22]. As a kind of macromolecular active substance formed by sulfation modification of polysaccharides, polysaccharide sulfate reflects its antioxidant ability by enhancing the scavenging ability of alkyl free radicals, hydroxyl radicals and superoxide anions[23][24][25].…”
mentioning
confidence: 99%